NEAR MISS. INVASIVE CANDIDIASIS AS A COMPLICATION OF A NEW CORONAVIRUS INFECTION COVID-19 (CLINICAL CASE) - Каменева, Евгения Александровна; Епифанов, Евгений Александрович; Трошков, Иван Андреевич; Малков, Николай Васильевич; Власов, Вадим Сергеевич; Рудаева, Елена Владимировна; Мозес, Вадим Гельевич; Елгина, Светлана Ивановна; Мозес, Кира Борисовна; Рыбников, Сергей Валерьевич; Центер, Яэль (Medicine in Kuzbass, 2023)
The purpose of the study – analysis of the clinical case "Near miss" on the basis of the Kuzbass Clinical Hospital named after S.V. Belyaev in a patient who had a new coronavirus infection COVID-19, complicated by fungal osteomyelitis of the bones of the facial skull.Materials and methods. A 73-year-old female patient was diagnosed with chronic osteomyelitis of the frontal bone, upper, medial and lower walls of the orbit, upper jaw and body of the zygomatic bone on the right, meningitis after suffering a new coronavirus infection COVID-19 of moderate severity. This complication required surgical intervention in the scope of resection bifrontal craniotomy, sequestrectomy, resection of the anterior and posterior walls of the frontal sinus, superior and medial walls of the right orbit, posterior ethmoid cells, osteonecrectomy of the upper jaw on the right, inferior wall and inferior orbital margin of the right orbit, lateral and lower walls of the nose on the right, zygomatic bone on the right, removal 1.3; 2.1; 2.2; 2.3 teeth. The course of the postoperative period was complicated by purulent meningitis. In the postoperative period, the patient was in the anesthesiology-reanimation department for 31 days, of which the first three days she was on prolonged mechanical ventilation, then she was transferred to spontaneous breathing.Results. Timely detected multidisciplinary lesion, observation of the patient with the involvement of doctors of maxillofacial surgery, neurosurgeons, otorhinolaryngologists, ophthalmologists-surgeons, neurologists, cardiologists, and anesthesiologists-resuscitators, made it possible to timely identify the resulting fungal infection and perform surgery.Conclusions. The presented clinical case is a vivid example of one of the serious complications of the new coronavirus infection COVID-19. Viral pneumonia increases the susceptibility of patients to bacterial and fungal superinfections, which complicates the clinical course of the disease in many critically ill patients. Given the difficulties associated with the diagnosis and management of this category of patients, there is an urgent need to study the epidemiology and characteristics of this secondary infection.
Keywords: COVID-19; invasive candidiasis; osteomyelitis of the bones of the facial skull; meningitis